Physiology of freezing of gait. Issue 5 (7th October 2016) - Snijders, Anke H.; Takakusaki, Kaoru; Debu, Bettina; Lozano, Andres M.; Krishna, Vibhor; Fasano, Alfonso; Aziz, Tipu Z.; Papa, Stella M.; Factor, Stewart A.; Hallett, Mark
Abstract : Freezing of gait (FOG) is a common and debilitating, but largely mysterious, symptom of Parkinson disease. In this review, we will discuss the cerebral substrate of FOG focusing on brain physiology and animal models. Walking is a combination of automatic movement processes, afferent information processing, and intentional adjustments. Thus, normal gait requires a delicate balance between various interacting neuronal systems. To further understand gait control and specifically FOG, we will discuss the basic physiology of gait, animal models of gait disturbance including FOG, alternative etiologies of FOG, and functional magnetic resonance studies investigating FOG. The outcomes of these studies point to a dynamic network of cortical areas such as the supplementary motor area, as well as subcortical areas such as the striatum and the mesencephalic locomotor region including the pedunculopontine nucleus (PPN). Additionally, we will review PPN (area) stimulation as a possible treatment for FOG, and ponder whether PPN stimulation truly is the right step forward. Ann Neurol 2016;80:644–659